2010
DOI: 10.1177/104063871002200513
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Feces versus Rectal Swabs for the Molecular Detection of Lawsonia Intracellularis in Foals with Equine Proliferative Enteropathy

Abstract: Abstract. The purpose of the current study was to compare the molecular detection rate of Lawsonia intracellularis between feces and rectal swabs collected from 42 foals with suspected equine proliferative enteropathy (EPE). Fecal samples and rectal swabs were processed for DNA purification by using an automated extraction system. The purified DNA was then analyzed by real-time polymerase chain reaction (PCR) for the presence of the aspartate ammonia lyase (aspA) gene of L. intracellularis. Absolute quantitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 17 publications
(52 reference statements)
0
16
0
Order By: Relevance
“…Several studies compared the qualitative sensitivity of rectal swabs versus stool specimens for the recovery and detection of various pathogens, such as Campylobacter fetus subsp. jejuni, vancomycin-resistant Enterococcus faecium (VRE), and Lawsonia intracellularis, by culturing and/or molecular quantification methods (12)(13)(14). These studies had mixed results, with some studies reporting comparable test sensitivity with either sample type (12)(13)(14) and others reporting significantly lower sensitivity with rectal swabs (15,16).…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…Several studies compared the qualitative sensitivity of rectal swabs versus stool specimens for the recovery and detection of various pathogens, such as Campylobacter fetus subsp. jejuni, vancomycin-resistant Enterococcus faecium (VRE), and Lawsonia intracellularis, by culturing and/or molecular quantification methods (12)(13)(14). These studies had mixed results, with some studies reporting comparable test sensitivity with either sample type (12)(13)(14) and others reporting significantly lower sensitivity with rectal swabs (15,16).…”
mentioning
confidence: 94%
“…jejuni, vancomycin-resistant Enterococcus faecium (VRE), and Lawsonia intracellularis, by culturing and/or molecular quantification methods (12)(13)(14). These studies had mixed results, with some studies reporting comparable test sensitivity with either sample type (12)(13)(14) and others reporting significantly lower sensitivity with rectal swabs (15,16). For quantitative testing, rectal swabs are believed to be inadequate due to the high variation in the quantity of fecal material on each swab and the difficulties in determining this quantity (17)(18)(19)(20).…”
mentioning
confidence: 99%
“…An antemortem diagnosis is generally confirmed by PCR detection of L intracellularis in faeces or a rectal swab and/or serology. In a recent study, faeces yielded a similar PCR detection rate for L intracellularis to that from rectal swabs and the authors concluded that rectal swabs should be considered an alternative sample type for PCR in EPE-suspected patients with reduced or no faecal output (Pusterla and others 2010b). …”
Section: Diagnosismentioning
confidence: 96%
“…Differences in sensitivity between different PCR and serological assays can also lead to divergent results. Among PCR assays, the use of real-time platform has been shown to yield the best sensitivity and to reduce the likelihood of cross- or carry-over contamination (ie, false positive results) (Nathues and others 2009, Pusterla and others 2010b, Richter and others 2010). …”
Section: Diagnosismentioning
confidence: 99%
“…PCR evaluation of diarrheic fecal samples is rewarding for establishing an infectious cause. [64][65][66][67][68] Malabsorptive enteric disease Malabsorption occurs in the horse when there is damage to the intestinal mucosa/ submucosa, which can result from inflammation that develops as the result of antigen/ antibody reactions, food intolerance, and true hypersensitivity lesions. The role of the cyathostomes must also be considered as they encyst and then can emerge in large numbers with disruption in the mucosa/submucosa that triggers fibrosis, which impedes absorption.…”
Section: Infectious Enteric Diseasementioning
confidence: 99%